Characteristics of pediatric pulmonary hydatid cyst in Mashhad, North East of Iran. - Seyed Javad Sayedi; Hanieh Zandi; Sepideh Bagheri (Reviews in Clinical Medicine, 2022)
Hydatid disease is an important health problem in endemic areas like Iran. Unlike adults, the occurrence of pulmonary hydatid cyst is greater than hepatic cysts in pediatric population. In this study we evaluated the characteristics of pediatric pulmonary hydatid cyst in our region. We reviewed the medical records of all children with the diagnosis of pulmonary hydatid cyst in Dr Sheikh’s children hospital between 2015-2019. 30 patients were enrolled during the study period. Diagnosis was confirmed using imaging and serology tests.Mean age of patients was 8.5±2.1 years (range:6-14 years). 73% were male and 80% were living in rural areas. All patients were symptomatic at presentation and the most frequent symptom was cough (76%) followed by dyspnea (43%). The most frequent site of involvement was the lower lobe of the right lung (30% of patients) and bilateral involvement was seen in 16.7% of patients. 13.3% of patients had simultaneous hepatic involvement. Complications were reported as follows: pleural effusion 30%, superinfection and abscess formation 16.7% and pneumothorax in one patient. All patients underwent surgical treatment. Lobectomy was performed in 5 cases (16.6%). Pulmonary hydatid cyst must be considered in children with respiratory symptoms in endemic areas. Early diagnosis might lower the risk of complications and lobectomies.